2006
DOI: 10.1016/j.nepr.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinically speaking: A communication skills program for students from non-English speaking backgrounds

Abstract: This paper reports on the design, delivery and evaluation of a pilot oral communication skills program for first year students in a Bachelor of Nursing (BN) degree at an Australian university. This program was introduced in 2004 to meet the needs of first year undergraduate students from non-English speaking backgrounds who had experienced difficulties with spoken English while on clinical placement in hospitals. The program consisted of early identification of students in need of language development, a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 7 publications
4
53
0
3
Order By: Relevance
“…They experienced difficulties in understanding conversations between patients and clinicians, how the use of technical terms and Australian idioms was like a 'third language' (Crawford & Candlin, 2013). Similar findings were reported in an earlier study and also included difficulty understanding handover reports as the nurses spoke quickly and used terminology and abbreviations with which students were unfamiliar (San Miguel et al, 2006).…”
Section: Participantssupporting
confidence: 68%
See 2 more Smart Citations
“…They experienced difficulties in understanding conversations between patients and clinicians, how the use of technical terms and Australian idioms was like a 'third language' (Crawford & Candlin, 2013). Similar findings were reported in an earlier study and also included difficulty understanding handover reports as the nurses spoke quickly and used terminology and abbreviations with which students were unfamiliar (San Miguel et al, 2006).…”
Section: Participantssupporting
confidence: 68%
“…Our findings indicated that males were welcomed and treated positively during their placements, which may indicate more of an acceptance of male students than shown in previous studies (O'Lynn, 2004;Stott, 2007). Poor language skills have been shown to have negative experiences during clinical placements (Mattila, Pitkäjärvi, & Eriksson, 2010) and that support prior to clinical placement can improve communication skills and confidence and lead to a positive clinical experience (San Miguel et al, 2006). It would appear that language literacy remains a real problem, with suggestions that linguistic support may not be taken up by some students.…”
Section: Send Them Homementioning
confidence: 40%
See 1 more Smart Citation
“…Studies have revealed that ESL students may experience challenges in clinical settings with the use of terminology, communicating or understanding patient requests, or providing explanations. [39,40] In a study by Bosher and Smalkoski, [39] when ESL students communicated with patients, CIs noted lack of eye contact, low volume speech, and inappropriate voice intonation. Therefore, as Starr [38] suggested, a positive instructor's response to language challenges is crucial to ensuring the learning of the continuing growing numbers of nursing students from culturally diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Authors further suggested that a specially designed clinically speaking program improved the experience of students from non-English speaking backgrounds during clinical placement and assisted the majority to successfully gain a satisfactory grade for their clinical placement [12].…”
Section: Literature Reviewmentioning
confidence: 99%